An evaluation of the knowledge and perceptions of pharmacy students on pharmacovigilance activities in Nigeria - Kanayo P. Osemene; Margaret. O. Afolabi (BMC Research Notes, 2017)
Abstract Background The use of the modified-prescription event monitoring technique has facilitated the understanding and reporting of pharmacovigilance (PV). However, in Nigeria, PV activities are largely misunderstood. Furthermore, there is a dearth of information on the knowledge and perceptions of pharmacy students on PV activities in relation to demographics. This study investigated and assessed the knowledge and perceptions of pharmacy students about pharmacovigilance as well as the demographic factors that are related to pharmacovigilance activities. Methods A cross-sectional survey was conducted among final year pharmacy students in three universities in months of January and February, 2016 with permission from the institutions and with written consents from 342 respondents. Pre-tested questionnaire was used to elicit information on the study objectives. Data were analysed using appropriate descriptive and inferential statistical techniques. Results The study revealed that the mean score on knowledge of pharmacy students on pharmacovigilance activities was 4.3 ± 0.18 which was significant according to gender (P < 0.001), students’ university (P < 0.001), and previous exposure to PV subjects (P < 0.001). Sixty-four percent of the students had positive perceptions about PV activities which was significant at P < 0.00 according to gender and their various universities. Less than half of the respondents 165 (48.2%) were able to correctly name the organisation that collates and document ADR reports in Nigeria. Only 21 (6.1%) of the respondents gave the correct answer to whether or not all possible ADRs of a drug can be determined during clinical trials or during pre-marketing phase of drug assessment. About 204 (59.7%) of the respondents erroneously believed that adverse reactions caused by cosmetics should not be reported. Conclusions Respondents have inadequate knowledge of PV activities. Therefore, pharmacy student educators should enhance students’ knowledge about PV through training, during clerkship, and lay more emphasis on relevant PV courses in the Pharmacy Curriculum.